High accuracy temperature and humidity sensors for next generation of HVACS - Thong, Edwin Kun Lin (2015)
Heating, ventilating, and air conditioning (HVAC) systems are used to provide ventilation and maintain air quality. The important components in a HVAC are temperature sensors, as they measure the temperature of the environment and transmit the readings to the controllers to take appropriate action. A large error in the measured value and the true value will result in an inefficient system performance and may affect the air quality of the environment. Sensors are calibrated before actual implementation to increase its reliability and performance. Regular calibration of the sensors ensures that the readings are still reasonably accurate. The two main approaches of calibration are laboratory calibration and field calibration. The aim of this project is to create a portable calibration system for the latter. The result will be a reduction in energy consumption for new and existing buildings without compromising comfort and air quality. Temperature sensors produce a change in resistance when subjected to changes in temperature. The temperature can be found by solving the relationship between the temperature and resistance equation. The two types of temperature sensors that will be the target of calibration are the RTD and the thermistor, which work on metal and semiconductor electrical characteristics described by two different temperature-resistance relationships. As such, each has its own program running its own specific computation. The unknown coefficients in each equation are solved by the least squares method via a collection of experimental readings called data sets. The coefficients are found and plugged back into respective equations to calculate the temperatures, with a given resistance. Experiments were then carried out for verification of this concept.